Real-Time Emotion Recognition System for Dynamic Real-World Environments - Madnani, Mayur (2023 16th International Conference on Developments in eSystems Engineering (DeSE), 2023)
Facial expressions are a direct and innate form of meaningful channel that conveys emotions non-verbally. Though considerable breakthroughs have been made in Automatic Factial Emotion Recognition (AFER), the research has been on lab-controlled datasets. Real-world scenarios pose expression-unrelated variations, such as illumination, occlusion, pose variations, skin-tone variation, subject identity bias, face deformation, motion blur, etc. There is a lack of data with such unconstrained conditions in contrast to the lab-controlled setting. With deep learning techniques, larger models bring significant accuracy but fail to work in real-time and are left unusable in real-world scenarios and even suffer from the explainability of the outputs. The research develops a lightweight Facial Emotion Recognition system for emotion recognition of facial images, which can operate in real-time and is suitable for use on devices with limited hardware resources. The developed FER system is comparable with previous research and SOTA models and also explainable with far fewer model parameters. With less than 600K model parameters, the proposed FER system achieves a weighted test accuracy of 60% on FER-2013 and 65% on FERPlus respectively, with an inference time of less than 560ms.